2022
DOI: 10.1360/nso/20220011
|View full text |Cite
|
Sign up to set email alerts
|

Digital medical education empowered by intelligent fabric space

Abstract: Medical education plays an important role in promoting the development of global medical science. Nevertheless, the intrinsic gap existing between institutional medical teaching and practical clinical tasks causes low education efficiency and students' weak initiative. Recent developments of sensing fabric and embedded computing, along with the advances in artificial intelligence (AI) and digital twin technology are paving the way for the transformation of medical research towards digitization. In this work, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…[301] Researchers are also developing intelligent textiles and clothing that sense signals from the wearer's body and the environment, perform on-body computing, and communicate the output with a central computer. [301] This so-called fabric computing has the potential to revolutionize digital education, [312] smart living, [313] health protection, and monitoring. [301]…”
Section: E-textilesmentioning
confidence: 99%
“…[301] Researchers are also developing intelligent textiles and clothing that sense signals from the wearer's body and the environment, perform on-body computing, and communicate the output with a central computer. [301] This so-called fabric computing has the potential to revolutionize digital education, [312] smart living, [313] health protection, and monitoring. [301]…”
Section: E-textilesmentioning
confidence: 99%
“…By assessing the strategy on the validation dataset, fast automatic augmentation, which Sungbin et al suggested, significantly increases the searching speed and reduces the time consumption [21]. In conjunction with studies on automated searching techniques, this work suggests a data augmentation technique used for crowd-counting task in a variety of contexts [22].…”
Section: Related Workmentioning
confidence: 99%
“…[ 33 ] In such an intelligent fabric space, medical students could receive operation training based on multifunctional fibers and digital‐twin technology to evaluate their manipulation performance and physical conditions in real time. [ 34 ]…”
Section: Health‐monitoring Agentsmentioning
confidence: 99%
“…[33] In such an intelligent fabric space, medical students could receive operation training based on multifunctional fibers and digital-twin technology to evaluate their manipulation performance and physical conditions in real time. [34] Considering that physical sensors based on multifunctional fibers can only monitor vital signs and physical activities, biochemical sensors are essential to assess the human health state at the biomolecular level. [35] Biofluids, such as saliva, [36] tears, [37] sweat, [38] and interstitial fluids, [39] are ideal analytes, as they can be retrieved noninvasively and contain a wealth of physiological information.…”
Section: Multifunctional Fibers For Information Acquisitionmentioning
confidence: 99%